Serum stimulation of CCR7 chemotaxis due to coagulation factor XIIa-dependent production of high-molecular-weight kininogen domain 5 - Ponda, Manish P. (Proc Natl Acad Sci U S A, 2016)
Chemokines and their receptors play a critical role in immune function by directing cell-specific movement. C-C chemokine receptor 7 (CCR7) facilitates entry of T cells into lymph nodes. CCR7-dependent chemotaxis requires either of the cognate ligands C-C chemokine ligand 19 (CCL19) or CCL21. Although CCR7-dependent chemotaxis can be augmented through receptor up-regulation or by increased chemokine concentrations, we found that chemotaxis is also markedly enhanced by serum in vitro. Upon purification, the serum cofactor activity was ascribed to domain 5 of high-molecular-weight kininogen. This peptide was necessary and sufficient for accelerated chemotaxis. The cofactor activity in serum was dependent on coagulation factor XIIa, a serine protease known to induce cleavage of high-molecular-weight kininogen (HK) at sites of inflammation. Within domain 5, we synthesized a 24-amino acid peptide that could recapitulate the activity of intact serum through a mechanism distinct from up-regulating CCR7 expression or promoting chemokine binding to CCR7. This peptide interacts with the extracellular matrix protein thrombospondin 4 (TSP4), and antibodies to TSP4 neutralize its activity. In vivo, an HK domain 5 peptide stimulated homing of both T and B cells to lymph nodes. A circulating cofactor that is activated at inflammatory foci to enhance lymphocyte chemotaxis represents a powerful mechanism coupling inflammation to adaptive immunity.